THE GROWING USE OF CHEMICAL FERTILIZERS IN AGRICULTURE AND ENVIRONMENTAL DEGRADATION WITH SPECIAL REFERENCE TO PRAYAGRAJ DISTRICT : कृषि में बढ़ता रासायनिक उर्वरकों का प्रयोग और पर्यावरण अवनयन जनपद प्रयागराज के विषेष संदर्भ में - Yadav, Monika (International Journal of Research -GRANTHAALAYAH, 2021)
English: Significant changes have taken place in the importance and form of agriculture from the beginning to the present period. In the Vedic period, the use of iron tools and later the discovery of irrigation techniques made people more efficient in agriculture, while in the British era, growing commercial crops like cotton and indigo brought about a big change and earning money became the main objective of agriculture. As a result of this, the food crisis has emerged as a major problem. The Green Revolution of the 1970s heralded a new era of rapid food production. One of the main catalysts for this revolution was the use of chemical fertilizers. Certainly, the Green Revolution solved the immediate food crisis, but heralded a harmful method for the future. We have to be ready to deal with the ill effects of it. Hindi: आदि काल से वर्तमान काल तक कृषि के महत्व तथा रूप में आमूलचूल परिवर्तन हुए हैं। वैदिक काल में लोहे के औजारों का प्रयोग तथा बाद में सिंचाई तकनीक की खोज से लोग कृषि में अधिक सक्षम हुए तो वहीं, ब्रिटिश काल में कपास और नील जैसी वाणिज्यिक फसलें उगाने से बड़ा बदलाव आया और धन कमाना कृषि का प्रमुख उद्देश्य हो गया। इसके दुष्परिणाम स्वरूप खाद्य संकट एक बड़ी समस्या के रूप में सामने आया। 1970 के दशक में आई हरित क्रान्ति ने तीव्र खाद्यान्न उत्पादन के एक नए युग का सूत्रपात किया। इस क्रान्ति का एक प्रमुख उत्प्रेरक रासायनिक उर्वरकों का प्रयोग रहा। निश्चय ही हरित क्रान्ति ने तात्कालिक खाद्यान्न संकट का समाधान किया किन्तु भविष्य के लिए एक हानिकारक पद्धति का सूत्रपात कर दिया। जिसके दुष्परिणामों से निपटने के लिए भी हमें तैयार रहना होगा।